# Khalid wrote the sequence below. x - 1, -2x + 2, 4x - 4, -8x + 8. Which formula can be used to find the 10th term of the sequence?

a_{10} = (x - 1)*(-2)^{10-1}

a_{10} = (x - 1)^{10-1}

a_{10} = (x - 1)*(2)^{10-1}

a_{10} = (x - 1)*(-2)^{10}

**Solution:**

Given, the sequence is x - 1, -2x + 2, 4x - 4, -8x + 8.

Common ratio, r = (-2x + 2) / (x - 1)

r = -2(x - 1) / (x - 1)

r = -2

Again, r = (4x - 4) / (-2x + 2)

r = 4(x - 1) / -2(x - 1)

r = -2

Therefore, the given series is in geometric progression.

We have to find the 10th term of the sequence.

The n-th term of a geometric sequence is given by a_{n} = ar^{n-1}

Here, a = x - 1, r = -2, n = 10.

a_{10} = (x - 1)(-2)^{10-1}

a_{10} = (x - 1)(-2)9

a_{10} = (x - 1)(256)

a_{10} = 256x - 256

Therefore, the 10th term of the sequence is a_{10} = (x - 1)(-2)^{10-1} or 256x - 256.

## Khalid wrote the sequence below. x - 1, -2x + 2, 4x - 4, -8x + 8. Which formula can be used to find the 10th term of the sequence?

**Summary:**

Khalid wrote the sequence x - 1, -2x + 2, 4x - 4, -8x + 8. The 10th term of the sequence is a_{10} = (x - 1)(-2)^{10-1} or 256x - 256.

Math worksheets and

visual curriculum

visual curriculum